Community‐Based Colorectal Cancer Screening in a Rural Population: Who Returns Fecal Immunochemical Test (FIT) Kits?. Issue 4 (21st September 2016) - Crosby, Richard A.; Stradtman, Lindsay; Collins, Tom; Vanderpool, Robin
Abstract: Purpose: To determine the return rate of community‐delivered fecal immunochemical test (FIT) kits in a rural population and to identify significant predictors of returning kits. Methods: Residents were recruited in 8 rural Kentucky counties to enroll in the study and receive an FIT kit. Of 345 recruited, 82.0% returned an FIT kit from the point of distribution. These participants were compared to the remainder relative to age, sex, marital status, having an annual income below $15, 000, not graduating from high school, not having a regular health care provider, not having health care coverage, being a current smoker, indicating current overweight or obese status, and a scale measure of fatalism pertaining to colorectal cancer. Predictors achieving significance at the bivariate level were entered into a stepwise logistic regression model to calculate adjusted OR and 95% CI. Findings: The return rate was 82.0%. In adjusted analyses, those indicating an annual income of less than $15, 000 were 2.85 times more likely to return their kits (95% CI: 1.56‐5.24; P < .001). Also, those not perceiving themselves to be overweight/obese were 1.95 times more likely to return their kits (95% CI: 1.07‐3.55; P = .029). Conclusions: An outreach‐based colorectal cancer screening program in a rural population may yield high return rates. People with annual incomes below $15, 000 and those not having perceptions of being overweight/obese may be particularly likely to return FIT kits.